2001
DOI: 10.1111/1467-9566.00273
|View full text |Cite
|
Sign up to set email alerts
|

Clinical actions and financial constraints: the limits to rationing intensive care

Abstract: This paper is concerned with the nature of rationing in intensive care. It reports a study of three intensive care units (ICUs) where resources were limited. We describe two conceptualisations of rationing: hard rationing, where there are absolute physical or financial constraints in place and soft rationing, in which clinicians and clinical managers, key actors in the organisation, can relax or remove apparently binding constraints. This paper demonstrates that, for the ICUs in this study, soft rationing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…[20][21][22] Over a 16-week period from January to May 2005, the authors conducted semistructured interviews, 1 hour in length, with 37 medical and public health professionals in the greater Pittsburgh area who played a decision-making role in vaccine allocation, whether from an administrative or direct care perspective. Investigators used preprepared questions to inquire about a person's initial and evolving awareness about the vaccine shortage and its institutional implications, and about the design, implementation, communication, and social acceptance of local vaccine rationing policy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Over a 16-week period from January to May 2005, the authors conducted semistructured interviews, 1 hour in length, with 37 medical and public health professionals in the greater Pittsburgh area who played a decision-making role in vaccine allocation, whether from an administrative or direct care perspective. Investigators used preprepared questions to inquire about a person's initial and evolving awareness about the vaccine shortage and its institutional implications, and about the design, implementation, communication, and social acceptance of local vaccine rationing policy.…”
Section: Methodsmentioning
confidence: 99%
“…20,22 People's ability to call on prior relationships provides a high degree of flexibility and innovation with which to handle local contingencies. If, however, a group exists at the fringes of personal and professional networks, then they may have less opportunity to advocate for their needs or present aid to others in need.…”
Section: Informal Arrangements and Relationships Facilitated Providermentioning
confidence: 99%
“…Lapsley and Melia (2001: 739–40) observed that intensive care teams are ‘tight‐knit’. Central to my analysis of this tight‐knit team is the firm physical boundary, which separates an ICU from other areas of the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Second, by developing a typology of professional responses to competing accountabilities, the study provides an analytical stepping stone for future research. While existing studies have provided examples of how frontline professionals seek to challenge budgetary limits and allocative decisions (e.g., Lapsley & Melia, 2001; Russell & Greenhalgh, 2014), the sociological literature on priority setting and rationing has yet to develop shared conceptualisations of how frontline professionals deal with distributive dilemmas. Third, the study brings the sociological debate on priority setting and rationing up to date with current developments in the medical field.…”
Section: Introductionmentioning
confidence: 99%